A construção e a utilização de instrumentos astronômicos antigos: um recurso pedagógico para o ensino e aprendizagem de geometria e trigonometria - Matos, Anderson Araujo (2020)
The present work had the use to verify if a research, a study, on the History of Astronomy and its relation with Mathematics, and the construction and use of ancient astronomical instruments, such as the Quadrant, and the Balestile, in the classroom, brought benefits for teaching and learning geometry and trigonometry. Research was also carried out on the importance of Meaningful Learning and Contextualization for the Teaching of Mathematics and Astronomy. The research was carried out in the city of Alagoinhas, Bahia, in a high school, in a 2nd grade class. To obtain the objectives of this research, a wrong method, Qualitative and Quantitative, was used, through observations, analysis of student grades, classes on the theme and applications of the theme of this research in the classroom. The students who participated in the research, obtain a significant improvement in your averages, as well as in their cognitive development. The educational product created in this work was a didactic sequence. The use of the History of Astronomy together with Mathematics and the construction and use of Balestile and Quadrant, old instruments, in the classroom can bring benefits to Mathematics classes, and thus achieve the goals of a good mathematical education.